2019
DOI: 10.1002/adfm.201907072
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Highly Efficient Controls of Reversible Topotactic Metal–Insulator Transitions through Proton Intercalation

Abstract: The ability to tailor a new crystalline structure and associated functionalities with a variety of stimuli is one of the key issues in material design. Developing synthetic routes to functional materials with partially absorbed non-metallic elements (i.e., hydrogen and nitrogen) could open up more possibilities for preparing novel families of electronically active oxide compounds. Here, we introduce a fast and reversible uptake and release of hydrogen in epitaxial ABO3 manganite films through an adapted low-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…The film was still ferromagnetic, with a smaller magnetic moment of 0.9 μ B /Mn at 10 K and 0.3 T (blue lines in Figure 1c,d), which differs from that of the oxygen‐driven transition into an antiferromagnetic insulator. [ 15,22 ] The slightly larger coercive field (blue line in the inset) might be attributed to the pinning of the magnetic domains by the non‐ferromagnetic regions in the film. [ 15 ] Although annealing the SrTiO 3 substrate in hydrogen also generated a magnetic signal, we confirmed that its value was negligible compared with that of the LSMO (Figure S2, Supporting Information).…”
Section: Reversible Metal–insulator Transition Via Annealing Ferromagmentioning
confidence: 99%
See 3 more Smart Citations
“…The film was still ferromagnetic, with a smaller magnetic moment of 0.9 μ B /Mn at 10 K and 0.3 T (blue lines in Figure 1c,d), which differs from that of the oxygen‐driven transition into an antiferromagnetic insulator. [ 15,22 ] The slightly larger coercive field (blue line in the inset) might be attributed to the pinning of the magnetic domains by the non‐ferromagnetic regions in the film. [ 15 ] Although annealing the SrTiO 3 substrate in hydrogen also generated a magnetic signal, we confirmed that its value was negligible compared with that of the LSMO (Figure S2, Supporting Information).…”
Section: Reversible Metal–insulator Transition Via Annealing Ferromagmentioning
confidence: 99%
“…At first glance, the metal–insulator transition observed in this study seems similar to the oxygen‐driven transition. [ 15 ] Although metal‐to‐insulator transitions occur when annealing LSMO films in a reducing environment (for example, in hydrogen (our work) or under a vacuum [ 15 ] ), we also successfully recovered the physical properties of the AG films by annealing the AH film in a reducing environment again (argon [our work]), rather than in an oxidizing environment (for example, oxygen [ 7,8,15,22 ] ). Furthermore, a much lower T a of 200 °C compared with the oxygen‐driven transition (>500 °C) [ 15 ] provides insight into hydrogen‐driven control because the much smaller size of the hydrogen ions enables faster hopping in an oxide, with a lower activation energy of 0.3–0.8 eV [ 24,25 ] (e.g., 0.8–1.0 eV for oxygen ions).…”
Section: Evidence Of Hydrogenic Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…275 Similar reversible phase transformations mediated by hydrogen and oxygen ions was also observed in VO 2 , ZnO, WO 3 , SrRuO 3 , La 1Àx Sr x MnO 3 , La 0.7 Sr 0.3 MnO 3 /SrIrO 3 superlattice films, etc. 18,164,[276][277][278][279][280][281] Water was also used as a gating medium for achieving hydrogen doping. 282 The ionization of water to form H + and OH À occurs when a bias voltage over 1.23 V is applied between an electrode and TMOs in water.…”
Section: Photo-electrocatalyst and Electrocatalystsmentioning
confidence: 99%